(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The article examines the pragmatic significance of a comic text in the process of speech communication and the pragmatic functions of comic effects in the process of speech communication. It has been established that in comic speech situations, language units create locative, illocutionary, and perlocutionary acts.